Private Participation in Urban Rail : A Resurgence of Public-Private Partnerships - Pulido, Daniel; Hirschhorn, Fabio (World Bank Group, Washington, DC, 2015)
Cities in the developing world are relying more on public-private partnerships (PPPs) to carry out the most complex and demanding of public works initiatives - the development of new urban heavy rail, or metros, usually involving underground lines. Most of the world’s metro systems are operated and were funded and built by public agencies. But developing country governments are shying away from the high cost and complexity of such systems and are acquiring more experience partnering with the private sector on infrastructure projects. Hence, the PPP approach, tried for metros with mixed results in the 1990s, has become more attractive. In the past five years, 2010-2014, five cities in Latin America and developing Asia have initiated seven new urban heavy rail lines using PPPs. In four of these projects, the PPPs are fully bundled, that is, they encompass design, financing, construction, and operations. It is too early to judge the overall performance of these seven projects, but some recommendations can be drawn from them as well as from earlier urban rail PPPs. The central lessons are the critical importance of a robust planning and management capacity in the public sector partner and the value of strong efficiency incentives for the private sector partners.